2020
DOI: 10.1021/acs.macromol.0c00254
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of Polymer Precursors to LixPON and LixSiPON Glasses: Materials That Enable All-Solid-State Batteries (ASBs)

Abstract: LiPON-like glasses that form lithium dendrite impenetrable interfaces between lithium battery components are enabling materials that may replace liquid electrolytes permitting production of all-solid-state batteries (ASBs). Unfortunately, to date, such materials are introduced only via gas-phase deposition. Here, we demonstrate the design and synthesis of easily scaled, low-temperature, low-cost, solution-processable inorganic polymers containing LiPON/LiSiPON elements. OPCl3 and hexachlorophosphazene [Cl2PN]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Similar MALDI analyses were done previously on Li x PONlike and Li x SiON precursors for lithium-ion battery applications. 37,38,48 Figure 1A,B shows negative-and positive-ion MALDIs of the Al-HMDS precursor, respectively. Both exhibit oligomeric peaks in the range of 300-500 m/z.…”
Section: Characterization Of Al-hmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar MALDI analyses were done previously on Li x PONlike and Li x SiON precursors for lithium-ion battery applications. 37,38,48 Figure 1A,B shows negative-and positive-ion MALDIs of the Al-HMDS precursor, respectively. Both exhibit oligomeric peaks in the range of 300-500 m/z.…”
Section: Characterization Of Al-hmdsmentioning
confidence: 99%
“…However, commodity scale production is challenging given the required specialized and expensive apparatus and low production rates (generally < 100 nm/min). [37][38][39] Here, we report a simple reaction of AlCl 3 with hexamethyldisilazane [HMDS, (Me 3 Si) 2 NH] in tetrahydrofuran (THF) or acetonitrile (ACN) at 60 • C/N 2 to produce an AlN precursor, Al(NHSiMe 3 ) 3 (denoted as Al-HMDS for convenience), as suggested by reaction (3). The byproduct Me 3 SiCl (boiling point = 57 • C) can be removed easily along with THF/ACN and excess HMDS by drying at 80 • C/1 h/vacuum (vac).…”
Section: Introductionmentioning
confidence: 99%
“…17,20,21,23 Recently, we demonstrated that the introduction of Si into Li polymer electrolyte (Li x SiPON) by shortening the distance between Li + binding sites. 21,24 With this background, here we investigate the effect of N introduction into amorphous Li 4 SiO 4 -like polymer analogs. Exploration of Li + -containing oxynitrides as electrolytes has been limited to thin-film batteries because of their low ionic conductivities (10 −6 S cm −1 ) at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, controlling the nitrogen content is key to achieving a higher ionic conductivity. , Both computational and experimental studies have demonstrated that amorphous rather than crystalline LiPON is a better Li conductor attributed to increases in diffusion/conduction due to reduction of overall electrostatic interactions and higher disorder within the material. ,,, Recently, we demonstrated that the introduction of Si into Li x PON polymer electrolytes enhances ionic conductivity and lowers the activation energy of the polymer electrolyte (Li x SiPON) by shortening the distance between Li + binding sites. , With this background, here we investigate the effect of N introduction into amorphous Li 4 SiO 4 -like polymer analogs.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of these extremely thin films requires gas-phase deposition techniques. However, the exploration of Li + conductive thin-film electrolytes by gas-phase deposition techniques, such as ALD, ion beam-assisted deposition, and pulse laser deposition, is still at an early stage as such methods are energy and equipment intensive, require high-cost process steps, and offer low deposition rates . Thus, there remains a considerable need to develop alternate methods of processing membranes with optimal conductivity as potential candidates for next generation ASSBs.…”
Section: Introductionmentioning
confidence: 99%